STRATEGI PENGELOLAAN HUBUNGAN INDUSTRIAL DALAM MEMINIMISASI KONFLIK INDUSTRI - Wardiningsih, Suprihatmi Sri (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2011)
ABSTRACT Industrial relations concerning the relationship between workers and employers as well as issues surrounding such as economic, social, political and cultural. When firms interact with many community stakeholders who are affected by decisions, policies and operations of the company. Number of stakeholders and different interests, causing potential conflicts in the company. The cause of the emergence of conflicts within the company, can be triggered by individual factors or organizational factors, which have the effect they are positive or negative. Conflict in the industry can be solved with the approach of competitors, collaborators, compromise, accommodator and avoidance of conflict. Keywords: Industrial Relations, Industrial Conflict, Man Power Marketing, Man Power Management.